Numerical Simulation on Dynamic Response of Existing Tunnel to Moving-Axle Loads under the Influence of Oblique Shield Crossing the Intersection Area - Pengcheng Jiang; Mengxi Zhang; Wurong Jia; Hui Wei; Akbar A Javadi (Shock and Vibration)
A 3D dynamic finite element model is developed to study the response of the existing tunnels’ concrete structure under the influence of different train speeds and undercrossing with fixed shield excavation. The intersection area of Metro Line 3 in Guangzhou and the intercity railway between Foshan and Dongguan is used as the case study. A programming idea simulating oblique moving-axle loads in the numerical model by using function expressions to constrain activity area is proposed. The Hilber–Hughes–Taylor time-integration scheme is used to calculate the dynamic response parameters of the double-channel rectangular cross section tunnels. Considering fixed excavation steps in the process of shield crossing, acceleration and deformation of the existing tunnels were analyzed under the moving-axle loads of trains at different speeds. From the perspective of the vibration and deformation of existing tunnels, shield excavation and moving speed have their own emphasis on the dynamic influence of the existing tunnel. In addition, the calculation results of the numerical simulation are in good agreement with the data obtained from some field tests, which further verifies the reliability of the calculation method of the numerical model. The results of this research can guide the arrangements for reinforcement measures for existing tunnels in the later stage.